Consumo de un pez por parte de la serpiente coral Micrurus alleni(Serpentes: Elapidae) en Costa Rica - Solórzano, Alejandro (Universidad de Costa Rica, 2005)
Micrurus alleni (Serpentes: Elapidae) in Costa Rica. The presence of a small specimen of the swamp eel Synbranchus marmoratus (84 mm total length) in the stomach contents of an adult coral snake Micrurus alleni with 692 mm total length from the Caribbean versant of Costa Rica is reported. This eel was swallowed headfirst.